2007
DOI: 10.1111/j.1654-1103.2007.tb02578.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of vegetation classification and plant indicators to assess grazing abandonment in Estonian coastal wetlands

Abstract: Question: What are the effects of grazing abandonment on the vegetation composition of Estonian coastal wetlands? Location: Vormsi Island and Silma Nature Reserve in western Estonia, Europe. Methods: Local knowledge and field reconnaissance were used to identify current and historical management levels of wetland sites within the west Estonian study area. Nine study sites, with varying management histories, were selected comprising an area of 287 ha. A total of 198 quadrats were taken from 43 distinct vegetati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 29 publications
0
49
0
Order By: Relevance
“…Although TWINSPAN has limited application to very complex frameworks (van Groenewoud 1992) it works well with simpler datasets and its hierarchic classification is very helpful, mainly when interpretations are made in comparison with DCA diagrams (McCune and Grace 2002; Tsiripidis et al 2007;Burnside et al 2007). It is one of few classification methods that provides a key for the identification of new samples; we propose this as a practical key for future use.…”
Section: Vegetation Classificationmentioning
confidence: 99%
“…Although TWINSPAN has limited application to very complex frameworks (van Groenewoud 1992) it works well with simpler datasets and its hierarchic classification is very helpful, mainly when interpretations are made in comparison with DCA diagrams (McCune and Grace 2002; Tsiripidis et al 2007;Burnside et al 2007). It is one of few classification methods that provides a key for the identification of new samples; we propose this as a practical key for future use.…”
Section: Vegetation Classificationmentioning
confidence: 99%
“…The generally low relief of Baltic coastal wetlands (between -0.28 and ?1.2 m) means that they can be inundated during periods of elevated sea level. Burnside et al (2007) identified six main plant communities with indicator species for Estonian coastal wetlands. These were Clubrush Swamp (CS), Reed Swamp (RS), Lower Shore (LS), Upper Shore (US), Tall Grass (TG), and Scrub and developing Woodland (SW).…”
Section: Study Areamentioning
confidence: 99%
“…( 1) TWINSPAN is internationally accepted as a hierarchical classification method that can simultaneously complete plot and species classifications and is widely used in vegetation ecology (Niall et al 2007;Nkosi, Barrett, and Brown 2016). Ordination techniques reveal correlations between the spatial distribution of plant communities and environmental factors, which might have extremely important ecological significance (Kajsa and Johanna 2005).…”
Section: Field Surveymentioning
confidence: 99%